Reversal of angiotensin ll-induced β-cell dedifferentiation via inhibition of NF-κb signaling - Hong Chen; Wenjun Zhou; Yuting Ruan; Lei Yang; Ningning Xu; Rongping Chen; Rui Yang; Jia Sun; Zhen Zhang (Molecular Medicine, 2018)
Abstract Background Type 2 diabetes mellitus (T2DM) is characterized by pancreatic β-cell failure, which arises from metabolic stress and results in β cell dedifferentiation, leading to β-cell death. Pathological activation of the renin–angiotensin system (RAS) contributes to increase cell stress, while RAS intervention reduces the onset of T2DM in high-risk populations and promotes insulin secretion in rodents. In this study, we investigated whether and how RAS induces β-cell dedifferentiation and the mechanism underlying this process. Methods In vitro, with the methods of quantitative real-time reverse transcriptase-PCR (qRT-PCR) and western blotting, we examined the change of cell identity-related gene expression, progenitor like gene expression, cellular function, and nuclear factor kappa b (NF-κb) signaling activity in β cell lines after exposure to angiotensin II (AngII) and disruption of RAS. In vivo, parallel studies were performed using db/db mice. Related protein expression was detected by Immunofluorescence analysis. Result Activation of RAS induced dedifferentiation and impaired insulin secretion, eventually leading to β-cell failure. Mechanistically, Angll induced β-cell dedifferentiation via NF-κb signaling, while treatment with lrbesartan and sc-514 reversed the progenitor state of β cells. Conclusion The present study found that RAS might induce β-cell dedifferentiation via angiotensin II receptor type 1 activation, which was promoted by NF-κb signaling. Therefore, blocking RAS or NF-kb signaling efficiently reversed the dedifferentiated status of β cells, suggesting a potential therapy for patients with type 2 diabetes.